ANALISIS FAKTOR YANG MEMPENGARUHI BIAYA AUDIT EKSTERNAL - Muhammad Anwar Sanusi; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This study is conducted to analyze factor influencing external audit fee of non-financial companies. Factor-factor influencing external audit fee is represented by size, profitability, risk, complexity, industry type, status of audit firm, external audit report lag, audit committee independence, account receivable, inventory. This research refers to research conducted by Nasser (2016).The population of study are all non-financial companies listed on the Kompas100 index for the periode 2014-2015. Total sample of 65 companies was determined by purposive sampling method. This study uses Ordinary Least Square for hypotheses testing.The result show that risk, complexity, industry type, status of audit firm were found to have a positive effect with statistical significance on external audit fee. Inventory was found to have a negative effect with statistical significance on external audit fee. Size, profitability, external audit report lag, audit committee independence, account receivable were not to have a significance effect on external audit fee, however it found that has a positive effect.